Empowerment of Muslim Family Education and Parental Resilience Towards Children with Special Needs at the “Purworejo Kita Semua” Foundation - Ummul Fadhilah; Siti Khusniyati Sururiyah; Deffi Andri Aspranata (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
This study aims to analyze the empowerment of family education grounded in Islamic values to enhance the resilience of parents of children with special needs at the “Purworejo Kita Semua” Foundation (Yayasan Purworejo Kita Semua [YPKS]) in Purworejo Regency. The study employed a qualitative approach with a descriptive research design. The research subjects included the foundation’s teachers and administrators as well as parents of children with special needs. Data were collected through interviews, observation, and documentation, and were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The study focuses on three main aspects: the conditions of parents of children with special needs, the forms of family education empowerment implemented by the foundation, and the impact of these interventions on parental resilience. The findings show that the parents’ initial conditions were marked by emotional stress, social stigma, and difficulties in parenting. The empowerment programs implemented by the foundation included an Islamic parenting program, JURASIK (Jum’at Berbagi itu Asyik / Friday Sharing is Fun) activities, Islamic spiritual activities, and lifelong healthy exercise programs integrating educational, social, and spiritual aspects. The impact of these programs is reflected in increased parental acceptance of their children’s conditions, stronger emotional resilience, greater optimism regarding their children’s future, and improved spiritual well-being. This study concludes that family education empowerment grounded in Islamic values can strengthen parental resilience through a comprehensive and sustainable approach, and it contributes practical insight into the development of supportive interventions for families of children with special needs.